Comprehensive genomic identification of cotton starch synthase genes reveals that GhSS9 regulates drought tolerance - Dai, Maohua; Yang, Xiaomin; Chen, Quanjia; Bai, Zhigang (Frontiers in Plant Science, 2023)
Starch metabolism is involved in the stress response. Starch synthase (SS) is the key enzyme in plant starch synthesis, which plays an indispensable role in the conversion of pyrophosphoric acid to starch. However, the SS gene family in cotton has not been comprehensively identified and systematically analyzed. In our study, a total of 76 SS genes were identified from four cotton genomes, and were divided into 5 subfamilies through phylogenetic analysis. Genetic structure analysis proved that SS genes from the same subfamily had similar genetic structure and conserved sequences. Cis-element analysis of SS gene promoter showed that SS gene promoter mainly contains light response elements, plant hormone response elements and abiotic stress elements, which indicate that SS gene not only plays a key role in starch synthesis but also may play an important role in abiotic stress response. Furthermore, we also conducted a gene interaction network for SS proteins. Silencing GhSS9 expression decreased the resistance of cotton to drought stress. These findings suggest that SS gene could be related to drought stress of cotton, which provides a theoretical support for further research on the regulation mechanism of SS genes on abiotic starch synthesis and sugar level.